Classificação de híbridos de milho por características produtivas, nutricionais e micotoxicológicas para nutrição animal - Vidal, Juliano Kobs (2024)
This thesis aimed to evaluate the influence of transgenics on the productive, nutritional, and mycotoxin characteristics of different corn hybrids produced in Brazil. The research was developed based on two main studies. In the first study, 150 samples from 50 corn hybrids were collected in a field experiment. Variance analysis was performed, and the hybrids were grouped by the Scott-Knott test, with a significance level of 5%. Most variables showed differences among the corn hybrids (P < 0.05), except for available phosphorus, damaged grains, and contamination by deoxynivalenol (DON) and zearalenone (ZEA) (P > 0.05). Productivity presented a positive correlation (P < 0.05) with feed formulation cost (r = 0.35), and negative correlations (P < 0.05) with crude protein (r = -0.42), digestible threonine (Dig. Thr) (r = -0.42), and digestible methionine + cystine (Met + Cys) (r = -0.42). The cost of feed formulation showed a positive correlation (P < 0.05) with fumonisins (FUM: FB1 + FB2) (r = 0.33) and ZEA (r = 0.29), and a negative correlation (P < 0.05) with crude protein (r = -0.74). In the second study, the effect of three important transgenic corn technologies — VT PRO3®, PowerCore® ULTRA, and Agrisure® Viptera 3 — on field characteristics, nutritional composition, and mycotoxin contamination was investigated in 215 samples of different corn hybrids over three years: 2020, 2021, and 2022. Crop yield was higher in VT PRO3® (9029 kg/ha in 2020, 5085 kg/ha in 2021, 9411 kg/ha in 2022) compared to PowerCore® ULTRA (8591 kg/ha in 2020, 4166 kg/ha in 2021, 8806 kg/ha in 2022) (P < 0.05). Total FUM levels were significantly higher in VT PRO3® (1180 μg/kg in 2020, 1657 μg/kg in 2021, 2566 μg/kg in 2022) compared to PowerCore® ULTRA (280.8 μg/kg in 2020, 414.0 μg/kg in 2021, 990.6 μg/kg in 2022) (P < 0.05). The apparent metabolizable energy balance (AMEn) was significantly higher (P < 0.05) in VT PRO3® in all years (P = 0.0007 in 2020, P = 0.0014 in 2021, P = 0.0001 in 2022). Regarding amino acids, in 2020, total and digestible isoleucine, leucine, and phenylalanine were higher in PowerCore® ULTRA compared to VT PRO3® (P < 0.05). In 2021, all total and digestible amino acids were significantly different between the corn technologies (P < 0.05), with higher concentrations in PowerCore® ULTRA. In 2022, PowerCore® ULTRA technology had a higher concentration of most total and digestible amino acids than VT PRO3® (P < 0.05), except for total lysine (P = 0.1480) and digestible tryptophan (P = 0.0909). The Agrisure® Viptera 3 technology was assessed only in 2020, having intermediate results for most of the variables studied. The studies demonstrated that there are variations in the productive, nutritional, and mycotoxin properties of the corn hybrids investigated, highlighting the need for a holistic approach that considers not only yield but also nutritional quality and food safety when selecting transgenic varieties for corn production.